PENGEMBANGAN PERMAINAN BOLA VOLI UNTUK MENINGKATKAN KETERAMPILAN PASSING - Akbar Nugraha (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
ABSTRACT This study aims to determine whether there is an effect of developing volleyball games to improve passing skills in volleyball. The principles of this research are quantitative descriptive. This study uses an experimental method with a one group pre-test post-test research design, the instrument is a passing test using a brady test, with the research subjects being all volleyball with a sample of 10 people. The data analysis technique used quantitative descriptive analysis with t-test as a hypothesis test as outlined in the discussion. The results of this study indicate that there is an increase in volleyball passing skills in volleyball with a t-value of 39.447 which is greater than the t-table value of 2.262.